The Importance of Sago Forest for Local Food Security and Climate Change Management on Small Island - Marcus Luhukay; Aryanto Boreel; Marthina Tjoa; Gun Mardiatmoko (Newinera Publisher, 2026)
Small Island worldwide are highly vulnerable to local food security and climate change. Therefore, appropriate spatial planning is needed to prevent the massive conversion of forest to non-forest areas, including sago, mangrove, and other natural forest on these small Island. This study used a method comprising a variety of activities, including field surveys, drone mapping, and interviews with sago owners and processors. The results showed that Ihamahu Village, on the small island of Saparua (Eastern Indonesia), had a sago forest area of ​​82.08 hectares with an average potential wet starch production of 450 kg per tree and a dry sago starch yield of 443 tons. This production enables local communities to process sago for household use and sell to the Saparua wholesale market. As sago has traditionally been a local food, the community continues to conserve forest in the region. In other words, sago potential has become a primary source of food security for local communities. With the ongoing conservation, the forest ecosystem is increasingly protected. The biomass content, especially of Mature Felling sago trees, was 30.33 tons per hectare, and this biomass would be even greater with the inclusion of Non-Mature Felling sago trees. This indicates that the sago forest ecosystem is capable of absorbing Greenhouse gas (GHG) emissions, thereby playing a significant role in mitigating climate change.